1999
DOI: 10.1046/j.1523-1755.1999.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of protein kinase C isoforms in streptozotocin-induced diabetic rats

Abstract: Streptozotocin increased blood glucose from 117.0 +/- 3.6 to 510.0 +/- 19.4 mg/dl (N = 8, P < 0.01) and induced albuminuria. PKC isoforms alpha, beta, delta, epsilon, and zeta were all detected in control animals. Western blot showed increased PKC alpha expression in kidney and heart (160% and 170%, respectively). PKC betaI, betaII, and delta expression was not influenced by hyperglycemia. PKC zeta was decreased in diabetic animals in both tissues by 60%. The membrane association of PKC alpha and PKC epsilon w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
86
4
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 62 publications
17
86
4
2
Order By: Relevance
“…Our findings differ somewhat from those reported in whole heart tissue from STZ-induced diabetic rats, in which an increase in the membrane association of one or several of the PKC isozymes ␣, ␤ 2 , ␦, and ⑀ has been reported (13,14,35,36). Differences between our results and those reported in whole heart tissue from STZ diabetic rats may reflect the physiological changes associated with the in vivo diabetic state, such as increased PKC-␣ expression in the nonmyocyte compartment of the myocardium (36). It must also be acknowledged that chronic exposure to a high glucose concentration may result in downregulation in the expression of some, but not all, PKC isozymes.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings differ somewhat from those reported in whole heart tissue from STZ-induced diabetic rats, in which an increase in the membrane association of one or several of the PKC isozymes ␣, ␤ 2 , ␦, and ⑀ has been reported (13,14,35,36). Differences between our results and those reported in whole heart tissue from STZ diabetic rats may reflect the physiological changes associated with the in vivo diabetic state, such as increased PKC-␣ expression in the nonmyocyte compartment of the myocardium (36). It must also be acknowledged that chronic exposure to a high glucose concentration may result in downregulation in the expression of some, but not all, PKC isozymes.…”
Section: Discussioncontrasting
confidence: 99%
“…In keeping with our findings, Hsieh et al reported recently that glucose-induced damage to proximal tubule cells is dependent on PKC-βI [14]. In addition, although there are conflicting results on which isoform(s) is(are) increased in the glomeruli of STZ-diabetic animals, with reports of increased levels of PKC-α [2, 10, 39], -βI [2,39,40], -δ [41] and -ɛ [10,41], PKC-βI seems to be the pathophysiological isoform [40,42]. Indeed, there is strong evidence that diabetes-induced mesangial cell damage occurs as a result of increased glucose uptake by GLUT1, which correlates with increased PKC-βI activation and fibronectin and collagen accumulation [1].…”
Section: Discussionsupporting
confidence: 90%
“…Studies have also detected altered levels of PKC isoforms in proximal tubular cells following exposure to high glucose concentrations, e.g. PKC-α, -ɛ [10] and -βI [14] specifically were found to be increased. These findings suggest that diabetes-induced alterations in the levels and activity of PKC isoforms may affect proximal tubular cell function, as well as having their already established effects on glomerular cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consistence with these findings, previous studies demonstrated significant increase in plasma creatinine and BUN [32][33][34] and serum urea levels [35] in diabetic rats compared to normal. The elevation of serum creatinine, uric acid, urea and UAE are reflection to impairment of kidney functions with development of diabetic nephropathy and loss of glomerular membrane permeability [36].…”
Section: Nc Group (N=10) Dm Group (N=4) Dm+afe Group (N=8) Dm+mfe Grosupporting
confidence: 79%